Pemetaan Tutupan Mangrove Dan Potensi Stok Karbon Pada Kawasan Restorasi Tangkolak Di Pesisir Cilamaya, Karawang, Jawa Barat - Andriwibowo Andriwibowo; Nana Suryana Nasution; Adi Basukriadi; Erwin Nurdin (Gunung Djati Conference Series, 2021)
Mangrove restoration through planting activities has been carried out on the coast of Cilamaya, Karawang, West Java. The planting activities were focused on the Tangkolak and Pasir Putih areas. Then, this study aims to map the mapping of mangrove cover in the Tangkolak and Pasir Putih restoration areas. The mapping method used for mapping is a Geographic Information System (GIS). The results showed that in Pasir Putih the area of mangrove restoration was 0.347 km2, residential areas were 0.243 km2, and 2.295 km2 for paddy fields or ponds. While in Tangkolak the area of mangrove restoration is 0.46 km2, settlements are 0.256 km2, and 2.413 km2 for paddy fields or ponds. The comparison of the mangrove restoration area between Tangkolak and Pasir Putih is 1.32 : 1. It is estimated that the potential carbon stock in the restoration area were ranging from 84 ton/ha (95%CI: 77-91 ton/ha) to 92 ton/ha (95%CI: 88-96 ton/ha). From the results of the study, it can be concluded that there is mangrove cover with potential carbon stocks resulting from the restoration of Tangkolak and Pasir Putih.